Examination of Yoga on Heart Rate Variability and Mindfulness Levels - Abdurrahman Aktop; Esin Kaplan (Selcuk University, 2023)
The aim of the study is to examine the effect of yoga practices on heart rate variability and mindfulness levels. A total of 52 women who did and didn't do yoga (Mean age= 30.25±5.58) voluntarily participated in the study. Heart rate variability was measured using the HeartMath brand emWave Pro+. Using the Emwave Pro device, the resting heart rate variability measurements were taken for 5 minutes in the sitting position. For this study, SDNN, RMSSD, MeanHR, LF/HF, and coherence parameters were evaluated. The Mindful Attention Awareness Scale (MAAS) was used to determine the mindfulness levels of the participants. According to the findings, a statistically significant difference was found in favor of the yoga group in the levels of SDNN (p gt;.005), meanHR (p gt;.020), and awareness (p gt;.041)". There is no significant difference in RMSSD (P =.050), LF/HF (P lt;.232), and Coherence (P lt;.718) parameters. As a result, yoga practices increase HRV. It is also an application that helps women to improve their mindfulness level.